Comparison and trends in outcomes of inborn and outborn infants born before 33 weeks’ gestation - Gergely Balazs; Melinda Vojtko; Mariann Marki; Samuel Lowe; Magdolna Riszter; Gusztav Belteki; Andras Balajthy (PLoS ONE, 2026)
Objective To compare clinical care and outcome of preterm infants born in a tertiary neonatal unit with those requiring early postnatal transport to the same unit, and analyze their trends over a 9-year period. Study Design A retrospective study of infants born before 33 weeks’ gestation between 2013 and 2021. Inborn (n = 913) and outborn (n = 133) infants were compared using logistic regression and trend analysis. Result Outborn infants more frequently required intubation in delivery room (59.4% vs. 32.3%, p < 0.001) and mechanical ventilation (69.2% vs. 44.5%, p < 0.001). They more frequently had severe intraventricular haemorrhage (IVH, 15% vs. 8.1%, p = 0.027) and had lower survival rate (88.7% vs. 91.9%, p = 0.02). Birth outside a tertiary neonatal unit increased the risk of severe IVH [odds ratio: 2.4 (95% confidence interval: 1.3–4.3)]. Only inborn infants showed decreasing trends in delivery room intubation (annual percentage change, APC: −21.2%, p < 0.001) and mechanical ventilation (APC: −8.3%, p = 0.001). Conclusion Outborn infants continue to require more invasive respiratory support and experience worse outcomes.